Forchlorfenuron Application Induced Parthenocarpic Fruit Formation without Affecting Fruit Quality of Cucumber - Li Su; Miaoqing Wang; Yuean Wang; Rahat Sharif; Nannan Ren; Chunlu Qian; Jun Xu; Xuehao Chen; Xiaohua Qi (Horticulturae, 2021)
The plant growth regulator forchlorfenuron is often applied to promote fruit setting and development in cucumber production. However, the effect of forchlorfenuron on the appearance and nutritional quality of cucumber is unknown. In the present study, forchlorfenuron was applied to female flowers 1 day before anthesis and at the day of anthesis. The application of forchlorfenuron successfully induced parthenocarpic fruit formation in cucumber. In addition, cytokinin-responsive genes were upregulated under forchlorfenuron treatment. Fruit treated with forchlorfenuron did not differ from pollinated fruit in shape, texture and major nutrients, such as protein, total flavonoids and vitamin C, with the exception of the lower phenolic acid content. Overall, our finding suggests that forchlorfenuron could be vital in promoting the parthenocarpic fruit set without altering the quality of cucumber.